Do specific parenting practices and related parental self-efficacy associate with physical activity and screen time among primary schoolchildren? A cross-sectional study in Belgium - De Lepeleere, Sara (BMJ Open, 2015)
OBJECTIVES: To assess the association between specific parenting practices and related parental self-efficacy with children's physical activity (PA) and screen time. Parental body mass index (BMI), family socioeconomic status (SES), and child's age and gender were examined as possible influencing factors. DESIGN: Cross-sectional. SETTING: January 2014, Flanders (Belgium). PARTICIPANTS: 207 parents (87.4% mothers) of children aged 6–12 years. OUTCOME MEASURES: Specific parenting practices, related parental self-efficacy, and children's PA and screen time. RESULTS: The majority of investigated parenting practices and related parental self-efficacy were not significantly associated with children's PA or screen time. However, children were more physically active if sports equipment was available at home (p<0.10) and if parents did not find it difficult to motivate their child to be physically active (p<0.05). Children had a lower screen time if parents limited their own gaming (p<0.01). The associations between parenting practices and related parental self-efficacy with children's PA or screen time were significant for parents with a normal BMI, for medium-high SES families and for parents of younger children. Furthermore, the association between the parenting relating factors and children's PA and screen time differed for boys and girls. CONCLUSIONS: In contrast to what we expected, the findings of the current study show that only a very few specific parenting practices and related parental self-efficacy were associated with children's PA and screen time. It was expected that parental self-efficacy would play a more important role. This can be due to the fact that parental self-efficacy was already high in this group of parents. Therefore, it is possible that parents do not realise how difficult it is to perform certain parenting practices until they are faced with it in an intervention. TRIAL REGISTRATION NUMBER: EC/2012/317.